Ergonomic Hazard Control Modeling for Informal Welding Workers in Greater Bandung: A Study on Musculoskeletal Disorders (MSDs) - Suherdin Suherdin; Supriyatni Kartadarma (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2025)
Ergonomic hazards are one of the causes of health problems in workers, including causing Musculoskeletal Disorders (MSDs) complaints. MSDs in workers affect physical fitness, reduce working days/hours, and ultimately are unable to work. WHO states that around 1.71 billion people have musculoskeletal conditions worldwide. MSDs complaints in Indonesia are a separate focus, research on MSDs complaints in the informal sector shows that 66% of workers experience MSDs complaints. One industry that has a high risk of MSDs is welding. The purpose of this study was to create an ergonomic hazard control model for informal welding sector workers in Greater Bandung. The research approach is quantitative, the type of analytical observational research with a cross-sectional design. The study population was informal welding sector workers in Greater Bandung, sample was taken using a purposive sampling technique, and the total number of samples in this study was 100 workers. The analysis used in this study was the chi-square test to see the relationship between variables. Modeling in this study will use binary logistic regression. The results of the study showed that working climate, working posture, workload, and physical fitness simultaneously influenced MSDs complaints of informal welding workers (p-value < 0.05). Based on these findings, the control of MSDs complaints can be achieved by effectively managing work climate, working posture, workload, and physical fitness.